2018
DOI: 10.1007/s40519-018-0526-x
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of social anxiety facets on disordered eating in pediatric obesity

Abstract: Level V, cross-sectional descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…These findings extend previous cross‐sectional research on fear of negative evaluation (Anderson et al, 2020; MacKey & la Greca, 2008; Trompeter et al, 2018) to suggest that fear of negative evaluation may predict subsequent weight/shape concerns in adolescents. While the mechanisms through which this longitudinal relationship may operate cannot be ascertained in the current study, fear of negative evaluation has been shown to make individuals more attentive to potential social threats (Rossignol et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…These findings extend previous cross‐sectional research on fear of negative evaluation (Anderson et al, 2020; MacKey & la Greca, 2008; Trompeter et al, 2018) to suggest that fear of negative evaluation may predict subsequent weight/shape concerns in adolescents. While the mechanisms through which this longitudinal relationship may operate cannot be ascertained in the current study, fear of negative evaluation has been shown to make individuals more attentive to potential social threats (Rossignol et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, these findings are all from Western samples. The only network analysis study on EDs in Iran reported that desiring to lose weight was the most central symptom among a large sample of Iranian adolescents (ages [12][13][14][15][16][17][18][19] and college samples (ages 18-54) in both males and females [31]; however, the findings regarding preadolescents are understudied.…”
Section: Network Theory: a Framework To Understand Ed Psychopathologymentioning
confidence: 99%
“…In addition to Western societies, SAD symptoms were associated with ED symptoms in non-Western adolescents [16,17]. Taken together, the literature has established a connection between social anxiety and ED symptoms among college students, adolescents, and ED treatment-seeking patients, and suggests that anxiety is an early predictor of later ED symptoms [10,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Youth with OV/OB were recruited from a multidisciplinary pediatric obesity clinic in the southern United States (Anderson et al, 2018). Data collection in the clinic is ongoing, so we examined all youth enrolled prior to April 13, 2018.…”
Section: Samplementioning
confidence: 99%